Development of Flash Card Instructional Media in the Context of Game-Based Volleyball Learning to Improve Collaboration Skills and Student Achievement - Iffah, Nur; Basyiruddin, Burhan; Aman, Mohd Salleh; Hidayatullah, Gilang Ginanjar; Sillah, Ebrima (Faculty of Sport and Health Sciences, 2024)
Effective education at the primary school level requires developing students' collaboration skills in an appropriate learning environment. However, there are still challenges in creating an environment that encourages student collaboration and improves their achievement. This study aims to develop flashcard learning media in the context of game-based volleyball learning with the aim of improving students' collaboration skills and achievement. The current development research (R&D) involved the stages of needs analysis, flashcard media design, media development, implementation in the learning environment, and evaluation of students at the elementary school level. The population of this study was 4th and 5th-grade elementary school students who received game-based volleyball learning. Based on the findings of the media expert validation test (83%; very valid) and the material expert test (87%; very valid), the results demonstrated that the development of flashcard learning media in the context of game-based volleyball learning was legitimate. Furthermore, with a significance level of 0.000<0.05, the paired sample t-test findings for student collaboration skills indicated a statistically significant relationship. Students' collaboration and academic performance can be enhanced by including flashcards as instructional media in a volleyball learning game.